A Framework for the Creation of Distributed Information Technology to Support the Scholarly Research аnd Organizational Activities of the NAS of Ukraine - Khimich, O.M.; Ivlichev, V.P.; Malchevskyi, I.A.; Bespalov, S.A.; Pustovoit, M.M.; Golotsukov, G.V.; Shchetynin, I.Ye.; Nikolenko, D.I.; Ivanov, S.M.; Kirsanov, V.F. (Science and Innovation, 2024)
Іntroduction. The development and implementation of distributed information technologies (DIT) in the operation of government bodies is in line with the Concept of e-Government Development widely recognized in the world and approved by the Cabinet of Ministers of Ukraine Decree No. 2250-р dated 13.12.2010. Problem Statement. The development of DIT for supporting the research and organizational activities (DIT ROA) of the NAS of Ukraine is a priority among the tasks for informatization of managerial and administrative activities of the NAS of Ukraine. Purpose. The purpose of the work under consideration is the development of DIT ROA of the NAS of Ukraine for the information of the documents processig related to the commencement, execution, control, recording, and closure of research and development (R&D) works. Materials and Methods. This research uses DIT creation methods based on the concept of lifecycle of processing a structured electronic document as basic information object for the design, development, operation, and maintenance of DIT. Results. The application of DIT ROA of the NAS of Ukraine has enabled to speed up the processing of above-mentioned documents, to ensure correctness and completeness of information about R&D works and the correctness and efficiency of statistical reports on the implementation of R&D works in institutions of the NAS of Ukraine. Conclusion. Creation of the Unified Distributed Information Technology for supporting the research and organizational activities of the NAS of Ukraine (UDIT ROA of the NAS of Ukraine) for the comprehensive informatization of research and organizational activities of the NAS of Ukraine has been proposed.